Authorship as a criterion for article production: an analysis of journals in the area of science education Qualis A1, A2, and B1 (Research, Society and Development, 2020)
The scientific environment is characterized by demands of productivity, fact that leads to discussions and debates about the quality of the produced works. The ethical conditions for the elaboration of scientific articles, such as that involving the real participation of the authors in the productions, have demanded the establishment of precise and clear criteria. In this sense, this study sought to identify and analyze authorship criteria in Qualis Capes A1, A2, and B1 journals in the area of Education, which have in their scope Science Education or Science Teaching, in order to identify the existence of guidelines to the possible authors. From this study, the objective was to discuss authorship criteria to improve the quality and reliability of scientific productions. For this, 44 journals were selected to analyze information about the authorship criteria. It was observed that the ORCID registration requirement for researchers is present in four journals; whereas guidelines on plagiarism are present in 11 journals; whereas only three journals require specific titling of the authors; and 18 journals refer to the authors' contribution criteria in scientific work. These data indicate that most of the journals evaluated present insufficient information to the authors, showing little concern with this part of the article production process. With the above, it is clear that research with journals should continue to be developed, seeking the criteria established by journals to ensure the fairness of the indication of authorship, as these contribute to the quality, ethics and dissemination of research by journals.